DNA Testing and Lineage in Muslim Societies: Yusuf al-Qaradawi’s Perspective within Contemporary Islamic and Social Studies - Masriadi, Masriadi (MUHARRIK: Jurnal Dakwah dan Sosial, 2024)
The determination of lineage (nasab) constitutes a fundamental aspect of Islamic family law, directly influencing a child’s rights and social status, including inheritance, maintenance, and guardianship. In the modern era, advances in science particularly in biotechnology have introduced new methods of verification through DNA (Deoxyribonucleic Acid) testing, especially in Indonesia. This development has sparked debates within Islamic legal discourse regarding whether such scientific methods can serve as a legitimate basis for establishing lineage. This study examines the perspective of Yusuf al-Qaradawi, one of the leading contemporary scholars, concerning the legality and position of DNA testing in lineage determination. The objective of this research is to conduct an in-depth analysis of Yusuf al-Qaradawi’s views on the use of DNA testing for lineage determination, as well as to trace the methodological and jurisprudential arguments underlying his reasoning. A qualitative approach with a library research method was employed. Data were collected from Yusuf al-Qaradawi’s writings, contemporary works on tafsir and fiqh, and references on modern Islamic family law. The findings indicate that Yusuf al-Qaradawi does not reject the use of DNA testing; however, he regards it as a supporting form of evidence (qarinah), rather than the primary proof in establishing lineage. According to him, lineage in Islam is primarily determined through a valid marriage, not merely by biological compatibility. Nevertheless, in specific circumstances such as disputes over lineage or cases of switched infants DNA testing may be used as a reference, provided that it does not contradict the principles of Sharia and the pursuit of public welfare (maslahah).